(untitled) (Global Journal of Management and Business Research, 2017)
This paper studies how information is transmitted across nations by focusing on three types of commodities: copper, soybean and wheat. The paper utilizes Johansen cointegration model, vector error correction model (VECM) and the generalized autoregressive conditional hetero skedastic model (GARCH) to investigate the price discovery and volatility spillover process of informationally-linked futures markets. The empirical results indicate that the models provide evidence to support the long-term equilibrium relationships and significant bidirectional information flows between copper futures markets in China and in the United States. Although innovations in one market can predict the futures volatility in another market, the volatility spillovers from U.S. futures to Chinese futures are more significant than the other way around. As for the soybean futures, there is a one-lag price transmission across markets, while no volatility spillover has been detected. As for the wheat futures, no information transmission is found across markets.